Методика вибору оптимальних енергетичних параметрів електрогідравлічного пресового обладнання - Якимчук, Дмитро Михайлович; Кармаліта, Анатолій Костянтинович (Eastern-European Journal of Enterprise Technologies, 2010)
The methods of choice of optimal energetic parameters of electro-hydraulic cutting presses of light industry are developed, what allows promoting energoefficiency and reliable work of press equipment